A European public sphere in coverage of the Greek sovereign debt crisis in the news programmes of ARD and ZDF - Kim Otto; Andreas Köhler (University of Würzburg, Department of Economics, 2016)
The present study examines news reporting during the Greek national debt crisis in the German television news programmes "Tagesschau" and "heute" and in the special broadcasts "Brennpunkt" on ARD and "ZDF spezial" on ZDF. The aim is to capture the extent to which the national German media are Europeanized within the context of coverage of the Greek national debt crisis, based on the representation of European actors and events. The study's results show that it is not really possible to speak of a Europeanized national public sphere in Germany as far as the coverage of the Greek national debt crisis is concerned.
Keywords: H63; H77; Y80; 330; Greek national debt crisis; European public sphere